Positional installation of contrast (PIC) and Redo-PIC cystography for diagnosis of occult vesicoureteral reflux - Kıvılcım Karadeniz-Cerit; David Terence Thomas; Raziye Ergun; Nurdan Yıldız; Harika Alpay; Sabahat İnanir; E Tolga Dağlı; Halil Tuğtepe (The Turkish Journal of Pediatrics)
To evaluate the value of Positional Installation of Contrast (PIC) and Redo-PIC cystography in patients with febrile recurrent urinary tract infection (f-UTI) where voiding cystourethrogram (VCUG) was negative. Patients with recurrent f-UTI with no reflux on VCUG referred to the outpatient clinic of Pediatric Urology, between June 2011 and June 2016 were included in the study. A PIC cystography was performed in all patients. When reflux was found, subureteric injection was performed. Urinary cultures were used for follow-up. Patients that continued having f-UTI, received redo-PIC cystography. PIC cystography was performed on 42 patients. The average age of patients was 8.0±3.6 years. Vesicoureteral reflux (VUR) was detected in 41 patients. Average follow-up time after PIC cystography was 44.6 months. Thirty-three patients (80.5%) were free of f-UTI after PIC cystography and concurrent subureteric injection. Eight patients continued to have recurrent f-UTI. Six of these patients underwent redo-PIC cystography and PIC-VUR was demonstrated in all patients. After an average follow up of 30.9 months, no f-UTI was seen in these patients. The success rate of 80.5% (33/41) after 1st PIC cystography and subureteric injection increased to 95.1% (39/41) after redo-PIC cystography in six patients. Patients with recurrent f-UTIs without VUR on VCUG are an important challenge. PIC cystography is an important tool in demonstrating occult VUR in these patients. We advise that PIC cystography is performed in all patients with recurrent f-UTI with negative VCUG and redo-PIC cystography in patients who continue to have f-UTI after 1st PIC cystography and subureteric injection.